Political Communication and Symbolic Power in Rural Indonesia: A Bourdieuian Perspective from Bojonegoro - Fatkhurohman Taufik; Nur’annafi Farni Syam Maella; Harliantara (Mediator: Jurnal Komunikasi, 2025)
This article examines the workings of symbolic power in local political communication in rural Indonesia, based on an ethnographic study in Bojonegoro Regency, East Java. Using Pierre Bourdieu’s framework of field, habitus, and forms of capital, economic, social, and cultural, the study explores how local actors accumulate and convert symbolic capital to sustain political legitimacy. Data were obtained through interviews, participant observation, and media discourse analysis, and thematically coded with NVIVO software. The findings show that social capital rooted in kinship and community networks, cultural capital expressed through religious knowledge and ritual participation, and economic capital manifested in patronage practices collectively shape perceptions of authority. Media platforms, both traditional and digital, reproduce these symbolic hierarchies by amplifying elite narratives and constraining alternative voices. The study contributes to the understanding of post-authoritarian democracy in Indonesia by revealing how symbolic power continues to structure political legitimacy beyond formal institutions. It argues for a more culturally embedded approach to democratic participation attentive to the interplay between communication, capital, and power.